Two Volcanic Tsunami Events Caused by Trapdoor Faulting at a Submerged Caldera Near Curtis and Cheeseman Islands in the Kermadec Arc. Issue 7 (3rd April 2023) - Sandanbata, Osamu; Watada, Shingo; Satake, Kenji; Kanamori, Hiroo; Rivera, Luis
Abstract: Two submarine earthquakes ( M w 5.8) occurred near volcanic islands, Curtis and Cheeseman, in the Kermadec Arc in 2009 and 2017. Following both earthquakes, similar tsunamis with wave heights of about a meter, larger than expected from their moderate seismic magnitudes, were observed by coastal tide gauges. We investigate the source mechanism for both earthquakes by analyzing tsunami and seismic data of the 2017 event. Tsunami waveform analysis indicates that the earthquake uplifted a submerged caldera around the islands. Combined analysis of tsunami and seismic data suggests that trapdoor faulting, or sudden intra‐caldera fault slip interacted with magma reservoir deformation, occurred due to magma overpressure, possibly in association with caldera resurgence. The earthquake scaling relationship for trapdoor faulting events at three calderas deviates from that for regular earthquakes, possibly due to the fault‐reservoir interaction in calderas. Plain Language Summary: Most tsunamis are generated by large earthquakes with seismic magnitudes M  > ∼7, but two moderate‐sized earthquakes with only M 5.8 near volcanic islands, north of New Zealand, caused unusual tsunamis with a maximum wave height of about a meter. In this study, we examine the unusual source mechanism of the volcanic earthquakes that excited unexpected tsunamis. By analyzing the records of tsunamis and seismic waves from the earthquakes, we suggest that the inside of a curved fault system beneath a submerged volcano with a caldera structure suddenly moved upward, together with a large intra‐caldera fault slip and a volume increase of a shallow magma reservoir. Overpressure created by magma accumulation beneath the submarine caldera recurrently induces meter‐scale tsunamis without significant ground motions, calling for attention to tsunami hazards from submarine calderas. Key Points: Unusual tsunamis were caused by two M w 5.8 volcanic earthquakes in 2009 and 2017 near Curtis and Cheeseman Islands in the Kermadec Arc By using tsunami and seismic data of the 2017 event, we suggest that a trapdoor faulting event occurred at a submerged resurgent caldera Trapdoor faulting events at calderas had abnormally large slips, possibly due to the fault‐reservoir interaction in calderas